Analisis Peran Bahasa Indonesia Dalam Membangun Identitas Nasional di Kalangan Mahasiswa Pada Era Digital - Tati Sherina Agustiana; Rafika Rasdin; Syifa Azzahra Khaerunnisa (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
This study aims to investigate the patterns of Indonesian use by students on social media, identify the factors that affect the use of the language, and formulate strategies to strengthen national identity through the good and correct use of Indonesian in the digital era. The research method used is a qualitative method with a literature analysis study approach. The results of the analysis show that social media has a significant role in shaping communication patterns and student lifestyles in the digital era. The use of Indonesian by students on social media tends not to be in accordance with the correct rules, influenced by global culture, the role of social media, understanding of the Indonesian language, social norms and values, and campus policies related to the Indonesian language. To strengthen national identity, the suggested strategies include Indonesian education and literacy, the role of communities and student organizations, and the implementation of campus policies that support the good and correct use of Indonesian on social media.